Epigenetic Gene Regulation: Epigenetic Therapies in the Precision Medicine Era (Adv. Therap. 8/2020). Issue 8 (10th August 2020) - Leite, Michel Lopes; de Oliveira, Kamila Botelho Sampaio; Cunha, Victor Albuquerque; Dias, Simoni Campos; da Cunha, Nicolau Brito; Costa, Fabricio F.
Abstract : In article number 1900184 Nicolau Brito da Cunha, Fabricio F. Costa and co‐workers review the current state of knowledge regarding the three main epigenetic mechanisms of gene regulation, which are DNA methylation, histone modification and non‐coding RNA expression. In addition, epigenetic therapies with "epidrugs" applied to precision medicine are discussed. This is a field that is receiving increased interest in the scientific community and in industry.